The Role of Self-Awareness and School Climate in Predicting Career and Work Future Orientation among Madrasah Aliyah Students - Metha Irmawayani Putri; Muhammad Fikri Pratama; Fithria Siti Hanifah; Fidia Hanan Zahara (Psympathic : Jurnal Ilmiah Psikologi, 2026)
This study aimed to examine the influence of self-awareness and school climate on career future orientation among Madrasah Aliyah (MA) students. Participants were adolescents aged 15–18 who completed questionnaires measuring self-awareness, perceptions of school climate, and career future orientation. Multiple linear regression was used to analyzed the contributions of each variable to students’ career future orientation. The results showed that both self-awareness and school climate positively predicted career future orientation, with school climate having a stronger impact. Therefore, adolescents’ career future orientation was shaped by both internal factors, such as self-awareness, and external factors, including supportive school environments. Students with higher self-awareness and a positive school climate tended to have more realistic and structured career future orientation. The result of this study showed the importance of integrating personal and environmental aspects in promoting adolescents’ career development. Schools were recommended to enhance climate, provide career guidance, and support programs that foster self-awareness. Future studies should explore additional factors influencing adolescents’ career future orientation using broader and in-depth methods.